The (Not So) Changing Man: Dynamic Gender Stereotypes in Sweden - Gustafsson Sendén, Marie; Klysing, Amanda; Lindqvist, Anna; Renström, Emma Aurora (Frontiers in Psychology, 2019)
According to Social Role Theory gender stereotypes are dynamic constructs influenced by actual and perceived changes in which roles women and men occupy (Wood & Eagly, 2011). Sweden is ranked as one of the most gender equal countries in the world, with a strong national equality discourse, and a relatively high number of men engaging in traditionally communal roles such as parenting and domestic tasks. This would imply a change towards higher communion among men. Therefore, we investigated the dynamics of gender stereotype content in Sweden with a primary interest in the male stereotype and perceptions of gender equality. In Study 1, participants (N = 323) estimated descriptive stereotype content of women and men in Sweden in the past, present or future. They also estimated gender distribution in occupations and domestic roles for each time-point. Results showed that the female stereotype increased in agentic traits from the past to the present, while the male stereotype had not changed. Furthermore, participants estimated no change for the future, and they overestimated how often women and men occupy gender nontraditional roles at present times. In Study 2, we controlled for participants’ actual knowledge about role change by either describing women’s change in agentic roles, or men’s change in communal roles (and a control). Participants (N = 648) were randomised to the three different conditions. Overall, the female stereotype increased in masculine traits, and this change was mediated by perceptions of social role occupation. The male stereotype did not change in femininity but decreased in masculinity when change focused on women’s role change in agentic roles. These results indicate that role change among women also influence perceptions of the male stereotype. Altogether, the results indicate that positive femininity is harder for men to gain, in that the only difference in gender stereotypes at present times occurred for this dimension.